Indoor thermal comfort of three garment factories in Dhaka, Bangladesh - Al Sayem Khan, Muhammed Abdullah (2013)
Bangladesh is a developing country with lots of factories of different types of products for export and local consumption. Garments are one of the top items for export. Around four million workers are working in the garment factories which are not well designed in the sense of the indoor thermal environment. Appropriate use of building materials and design contributes to reducing the consumption of energy and indoor heat. Each month workers are having sickness related to frequent temperature difference in work place. As a result, the production of factories is being affected due to the employees’ health. The aim of this research is to measure the indoor environment quality and building related illness (BRI) within selected garment factories. The research was done using two methods. The empirical data collection by thermal data logger was done to measure the indoor temperature and the questionnaire survey at the work places were for BRI. The field study was conducted for one year. The collected data were recorded in different months for the whole year. Data collection was carried out for duration of seven days in winter and three months in summer. Thermal behavior evaluation was done by comparative analysis between indoor and outdoor temperature of factory buildings. In selected factory buildings, indoor air temperature from 12pm to 2pm was 1.58°C to 4.63°C above the normal 32°C. The comfort evaluation of indoor thermal environment indicated that indoor becomes uncomfortable for 1-8 hours from 11pm to 6pm when workers working inside the factory at work place. The findings of this research are that the indoor environment of factory building is uncomfortable for work at day time during both winter and summer. The existing condition does not help the factory workers as it is not comfortable and also contributes to BRI. The uncomfortable indoor thermal environment needs to be improved by employers or factory owners to provide a better healthy environment for workers.